APPLICATION OF A GENRE-BASED APPROACH WITH AUDIO VISUAL AID TO IMPROVE THE WRITING ABILITY OF CLASS 11 STUDENTS OF SERDANG BEDAGAI MADRASAH ALIYAH - Herlina Herlina; Yulia Arfanti (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this study was to determine the effectiveness of applying GBA with Audio Visual Media in Teaching Listening to improve writing skills in grade 11 students at MANSB. The research subjects were all students of class XI MANSB. The procedure for this research includes: Preparing the GBA learning model; Determination of the treatment class/group, namely the control group and the experimental group, Conducting pre-tests, Conducting teaching and learning activities (KBM) in the experimental class and control class with the GBA learning model, Conducting Post-tests, and Analyzing data. The learning outcomes in the experimental class (Pre-Test) were 36 students, 60.00. and in the control class (Pre-Test) of 35 students, most students (13 students or 37%) got scores in the range50.01 - 60.00.The learning outcomes in the experimental class (Post-Test) were 36 students, the majority (8 students or 22%) got the core in the82.51 - 88.33.and in the control class (Post-Test) of 35 students, most of the students (12 students or 34%) got scores in the62.51 - 70.00.